Antimicrobial Resistance and Presence of Class 1 Integrons Among Different Serotypes of Salmonella spp. Recovered From Children with Diarrhea in Tehran, Iran - Eshaghi Zadeh, Seyedeh H.; Fahimi, Hossein; Fardsanei, Fatemeh; Soltan Dallal, Mohammad Mehdi (Infectious Disorders - Drug Targets, 2020)
Background: Salmonellosis is a major food-borne disease worldwide. The increasing prevalence of antimicrobial resistance among food-borne pathogens such as Salmonella spp. is concerning. Objective: The main objective of this study is to identify class 1 integron genes and to determine antibiotic resistance patterns among Salmonella isolates from children with diarrhea. Methods: A total of 30 Salmonella isolates were recovered from children with diarrhea. The isolates were characterized for antimicrobial susceptibility and screened for the presence of class 1 integron genes (i.e. intI1, sulI1, and qacEΔ1). Results: The most prevalent serotype was Enteritidis 36.7%, followed by Paratyphi C (30%), and Typhimurium (16.7%). The highest rates of antibiotic resistance were obtained for nalidixic acid (53.3%), followed by streptomycin (40%), and tetracycline (36.7%). Regarding class 1 integrons, 36.7%, 26.7%, and 33.3% of the isolates carried intI1, SulI, and qacEΔ1, respectively, most of which (81.8%) were multidrug-resistant (MDR). Statistical analysis revealed that the presence of class 1 integron was significantly associated with resistance to streptomycin and tetracycline (p = 0.042). However, there was no association between class 1 integron and other antibiotics used in this study (p > 0.05). Conclusion: The high frequency of integron class 1 gene in MDR Salmonella strains indicates that these mobile genetic elements are versatile among different Salmonella serotypes, and associated with reduced susceptibility to many antimicrobials.
Keywords: children